Características socioeconómicas de los productores de cacao orgánico de la parroquia Rio Bonito del cantón El Guabo año 2012 - Chuya Chuya, Luis Alfredo (2013)
The general and specific competences developed for research, criticism, self-criticism and analysis, allow to manage criteria for the diagnosis and intervention of the various social, economic, political, dental and cultural problems, being this exercise Includes the following.